Long-term Health-related Quality of Life Following Esophagectomy: A Nonrandomized Comparison of Thoracoscopically Assisted and Open Surgery. Issue 6 (June 2017) - Barbour, Andrew P.; Cormack, Orla M. Mc; Baker, Peter J.; Hirst, Jodi; Krause, Lutz; Brosda, Sandra; Thomas, Janine M.; Blazeby, Jane M.; Thomson, Iain G.; Gotley, David C.; Smithers, Bernard M.
Abstract : Objective: The aim of this study was to assess long-term health-related quality of life (HRQL) in patients after thoracoscopic and open esophagectomy. Summary of Background Data: Trials comparing minimally invasive with open transthoracic esophagectomy have shown improved short-term outcomes; however, long-term HRQL data are lacking. This prospective nonrandomized study compared HRQL and survival after thoracoscopically assisted McKeown esophagectomy (TAMK) and open transthoracic Ivor Lewis esophagectomy (TTIL) for esophageal or gastroesophageal junction (GEJ) cancer. Methods: Patients with esophageal or GEJ cancer selected for TAMK or TTIL completed baseline and follow-up HRQL assessments for up to 24 months using the EORTC generic and disease-specific measures, QLQ-C30 and QLQ-OES18. Baseline clinical variables were examined between the treatment groups and changes in mean HRQL scores over time estimated and tested using generalised estimating equations with propensity score (generated by boosted regression) adjustment. Results: Of the 487 patients, 377 underwent TAMK and 110 underwent TTIL. Most clinical variables were similar in the 2 groups; however, there were significantly more patients with AJCC stage 3 disease who underwent TTIL than TAMK (54% vs 32%, P < 0.01) and this was reflected in the survival data. Mean symptom scores for pain were significantly higher in the TTIL group than in TAMK for 2 years postoperatively ( P = 0.036). In addition, mean constipation scores were significantly higher for the TTIL group, with a 15-point difference in mean score at 3 months postoperatively ( P = 0.037). Conclusions: This large comprehensive nonrandomized analysis of longitudinal HRQL shows that TTIL is associated with more pain and constipation than TAMK. Abstract : Supplemental Digital Content is available in the text